Re-Desain Interior Kapal Ambulans Terhadap Jalur Akses Pasien Berdasarkan Ergonomi dan Perhitungan Teknis - Naufall Vassanove Audiansyah (Fakultas Teknik, 2026)
Sea transportation is crucial for emergency medical evacuation in archipelagic regions. However, the existing catamaran ambulance ship produced by PT Blambangan Bahari Shipyard possesses a critical geometric clash in its access pathway. The narrow 700 mm partition door and the limited 1,702.83 mm turning radius at the stern hinder the stretcher loading process, significantly reducing the evacuation efficiency. This research aims to analyze the existing condition, determine the ergonomic access requirements, redesign the interior layout, and evaluate the technical characteristics, particularly the center of gravity and intact stability of the vessel. The redesign process utilized a parent design Approach by preserving the original hull form. The interior spatial requirements were established using Indonesian anthropometric data combined with the Ministry of Health's ambulance standards. 3D modeling and hydrostatic calculations were conducted using Maxsurf student version software, while the interior visualization was developed using 3D modeling software. The result shows that the main access was relocated to the bow area using a weathertight door with a 1.208,55 mm width to enable straight axial loading. The central partition was widened to 1.250 mm, and the corridor Clearance was expanded to 1.682,09 mm by replacing the forward reclining seats with a side-facing bench seat. Vital medical equipment, including the central oxygen supply, was integrated flush to the wall inside the cabin. The technical calculation of the new design generated a Lightweight Tonnage (LWT) of 3,969 tonnes and a Deadweight Tonnage (DWT) of 2,534 tonnes. The intact stability evaluation across four operational load cases proved that the redesigned ambulance ship passed all safety criteria mandated by IMO A.749(18) and the HSC Code 2000, ensuring optimal and safe medical evacuation.
Finalisasi oleh Agus 3 agustus 2026
Keywords: Ambulance Ship; Interior Redesign; Ergonomics; Intact Stability; Maxsurf